Pharyngeal‐sparing radiation for head and neck carcinoma of unknown primary following TORS assisted work‐up. (14th August 2019) - Grewal, Amardeep S.; Rajasekaran, Karthik; Cannady, Steven B.; Chalian, Ara A.; Ghiam, Alireza F.; Lin, Alexander; LiVolsi, Virginia; Lukens, John N.; Mitra, Nandita; Montone, Kathleen T.; Newman, Jason G.; O'Malley, Bert W.; et al.
Abstract : Objective: In patients with head and neck carcinoma of unknown primary (HNCUP;pT0) following TORS‐assisted workup, we have adopted a pharyngeal‐sparing radiation therapy (PSRT) approach targeting only the at‐risk neck and omitting treatment of the pharynx. We report outcomes following PSRT, and compare to institutional historical control subjects who received pharyngeal‐targeted RT (PRT). Methods: Between 2009 and 2018, 172 patients underwent TORS‐assisted endoscopy as part of their workup for HNCUP. Following TORS, 54 patients had pT0 disease, of which 45 received RT. Forty‐nine percent received PSRT and 51% received PRT. Results: No statistically significant differences existed between the PSRT and PRT groups with respect to overall nodal distribution, p16 positivity (55% vs. 43%, P = .12), neck dissection rates (77% vs. 65%, P = .51), and administration of chemotherapy (55% vs. 65%, P = .55). Median follow‐up for PSRT and PRT groups were 24 and 28 months, respectively ( P = .04). Two‐year RFS was 86% and 74% for PSRT and PRT patients, respectively (log‐rank P = .30). Three and six patients recurred after PSRT and PRT, respectively. Two‐year OS for PSRT and PRT patients was 91% and 74%, respectively (log‐rank P = .31). Compared to PRT, PSRT was associated with statistically significantly less: grade 2+ mucositis (18% vs. 91%, P  < .01), new opioid requirement (27% vs. 91%, P  < .01), mean weight loss during RT (6.2 lbs vs. 17.4 lbs, P  < .01), feeding tube placement during RT (5% vs. 43%, P  < .01), and treatment‐related unplanned hospitalizations (9% vs. 39%, P = .04). Conclusion: Following TORS‐assisted management of patients with pT0 HNCUP, we observed reduced toxicity following PSRT compared to PRT without apparent compromise of disease cure. Level of Evidence: Level 3 evidence, retrospective review comparing cases and controls Laryngoscope, 130:691–697, 2020